Does economic inequality breed political inequality?. Issue 8 (17th November 2018) - Houle, Christian
ABSTRACT: Does economic inequality generate political inequality? While there is a large literature on the effect of inequality on regime change and support for democracy, there is little research on its effect on political equality across socioeconomic positions. Yet democracy and political equality, although related, are distinct concepts. While political power tends to be more evenly distributed in democracies than in autocracies, there is substantial variation in both regime types. This study argues that economic inequality should decrease political equality through multiple mechanisms: (1) it increases the resources of the rich relative to the poor; (2) it widens the gap in policy preferences across income groups; (3) it reduces participation; and (4) it depresses support for democracy. Using three measures of inequality and data on more than 140 countries between 1961 and 2008, it was found that economic inequality tends to increase political inequality, even when one controls for the level of democracy. Results hold when the sample is restricted by regime type. Finally, evidence in favour of the mechanisms is provided.